2016
DOI: 10.1075/ld.6.1.03svi
|View full text |Cite
|
Sign up to set email alerts
|

Nodding and note-taking

Abstract: The paper studies the activity of note-taking in interactions between a university student counselor and an undergraduate student. The study is based on authentic videotaped discussions recorded in a Finnish university. The study concentrates on sequences consisting of a question, an answer, and the taking of notes. The aim of the paper is to present a detailed multimodal analysis on how the note-taker moves from not writing to writing and how nodding is used in both receiving the answer and indicating the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 31 publications
(41 reference statements)
1
8
1
1
Order By: Relevance
“…Previous conversation analytic research on counselling has addressed various environments, such as academic supervision and student counselling (Hazel and Mortensen, 2014;Svinhufvud, 2016;Vehviläinen 2003), genetic counselling (Lehtinen, 2013;Sarangi, 2009) and HIV counselling (Miller and Silverman, 1995;Silverman, 1997). Tele-mediated interaction, such as email and telephone counselling, has been examined (Lamerichs and Stommel, 2016;Woods et al, 2015).…”
mentioning
confidence: 99%
“…Previous conversation analytic research on counselling has addressed various environments, such as academic supervision and student counselling (Hazel and Mortensen, 2014;Svinhufvud, 2016;Vehviläinen 2003), genetic counselling (Lehtinen, 2013;Sarangi, 2009) and HIV counselling (Miller and Silverman, 1995;Silverman, 1997). Tele-mediated interaction, such as email and telephone counselling, has been examined (Lamerichs and Stommel, 2016;Woods et al, 2015).…”
mentioning
confidence: 99%
“…Similarly, Muntigl et al (2012) observed differences in the "nod's trajectory (shallow vs. deep), rate (slow vs. fast) and number (single vs. double vs. multiple)" (p. 11). Contrary to Birdwhistell's account, I observe in contemporary literature a tendency toward organizing nods in dichotomies such as "expansive" versus "less expansive" (Whitehead, 2011), "deep" versus "shallow" (Muntigl et al, 2012), and "big" versus "small" (Svinhufvud, 2016). Moreover, it has been noted that nods may start with an upward or with a downward movement (Aoki, 2011;Oshima, 2014;Svinhufvud, 2016).…”
Section: Head Nodsmentioning
confidence: 82%
“…As we have seen, a stepwise transition occurs from the performance of being stuck to a writing posture and to the actual writing itself (cf. Svinhufvud, 2016). Before shifting her gaze toward the worksheet and picking up her pen, Stella takes off her glasses, yawns, adjusts her hair and plays with her pen.…”
Section: Excerpt 1 Writing Notesmentioning
confidence: 99%